A method for recovering an intracellular Polyhydroxyalkanoates (PHA). - Hassan, Mohd Ali; Mohammadi, Mitra; Abd Razak, Nor Asma; Chong, Mei Ling; Shirai, Yoshihito; Wan Yunus, Wan Md Zin; Abd. Aziz, Suraini; Abdullah, Amirul Al-Ashraf; Che Man, Hasfalina; Anis, Siti Nor Syairah; Phang, Lai Yee (2010)

(untitled)
The present invention relates to a method to recover an intracellular polyhydroxyalkanoates (PHA). The method includes the steps of (a) separating culture medium containing PHA-rich cells using centrifugation, (b) rinsing pellet obtained from setp (a) with distilled water, (c) freeze-drying pellet obtained in step (b), (d) adding distilled water to the freeze-dried sample, (e) separating non-PHA cellular material (NPCM)from PHA granules, (f) washing the pellet containing PHA from step (e) by distilled water and centrifuging for producing final pellet, and (g) freeze-drying the pellet produced from step (f).